Pentingnya Ekonomi Desa Melalui Terselenggaranya Badan Usaha Milik Desa (BUMDes) pada Desa Koijabi Kecamatan Aru Tengah Timur - Yohanes Zefnath Warkula; Yustinus Lambyombar (Program Studi Akuntansi PSDKU Universitas Pattimura, 2021)
This service aims to socialize the importance of the village economy through theimplementation of Village Owned Enterprises (BUMDes) for village officials and villagecommunities as a basis for improving abilities both individually and as village institutions inKoijabi Village, Aru Tengah Timur District. Problem identification is carried out as an initialstep to formulate what will be used as material for system design and training materials in thisservice activity. Conducted a field survey to Koijabi Village, Central-Eastern Aru District asa place to carry out activities, then conducted training, socialization and discussions with thevillage to identify problems related to the formation of BUMDes. The long term of this PkMprogram is Community Empowerment. Through the creation of Village-Owned Enterprises(BUMDes) in Koijabi Village, Aru Tengah Timur District, the formation of BUMDes requiresHuman Resources (HR) who really understand the ins and outs of management and are ableto market the products managed through BUMDes. Provide understanding to the KoijabiVillage Community for synchronizing programs from the central government to villages aboutBUMDes, and for better structuring the village economy.